Metastatic synovial sarcoma: Experience from a tertiary care center from India - K Govind Babu; Rajesh Patidar; C Lakshmaiah Kuntegowdanahalli; Lokanatha Dasappa; Linu Abraham Jacob; Suresh Babu; A H Rudresha; Lokesh N Kadabur; L K Rajeev; Deepak Koppaka; Vikas Asati (Indian Journal of Medical and Paediatric Oncology)
Background: Synovial sarcoma represents 8% of all soft-tissue sarcoma (STS). It is a high-grade STS, and 50% of patients develop metastasis. The most common site of metastasis is the lungs, lymph nodes followed by bones. Ifosfamide-based chemotherapy is associated with improved outcome. In this study, we report our experience of metastatic synovial sarcoma according to primary sites, metastatic pattern, and their outcome. Materials and Methods: This was a retrospective observational study carried out at our institute from January 2013 to December 2016. The aim of our study was to evaluate the pattern of metastasis, response to chemotherapy, and survival in patients with metastatic synovial sarcoma. Results: Over a period of 4 years, 43 patients with metastatic synovial sarcoma were diagnosed with median age of 30 years. Nearly 70% of patients had lung metastasis, other site of metastasis were lymph node, bone, and liver. Thirty patients received chemotherapy with a combination of ifosfamide and doxorubicin. The overall response rate was 87% with median progression-free survival of 8 months. Patients with lung only metastasis had better survival compared with nonpulmonary metastatic site (18 months vs. 12 months). The median survival was 18 months. Conclusion: Metastatic synovial sarcoma is chemoresponsive tumor with lung being the most common metastatic site. Patients with lung only metastasis had a better outcome than nonpulmonary metastasis.